2013
DOI: 10.2355/isijinternational.53.1471
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive Wear Behaviour of Heat Treated En31 Steel

Abstract: Ni-Cr-Mo steels are widely used in machine part members, gears and shafts. Steels with higher carbon content (~1%) are used for heavy machine parts and bearings. Abrasive wear resistance is often a very important requirement for these high carbon steels, apart from sliding wear properties. In the present study, En31 steel was subjected to varying heat treatments to generate different microstructures. An attempt has been made to correlate the two body abrasive wear resistance with the bulk hardness and microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…At higher tempering temperatures, precipitation of iron rich carbides indicates the decomposition of martensite into ferrite and Fe 3 C, which is slightly enriched with Cr. A similar sequence has been reported for a study on En31 steel [40]. The XRD patterns of the as-quenched, quenched-tempered 523 K, quenched-tempered 723 K and quenched-tempered 923 K D2 steel samples are shown in Fig.…”
Section: 82supporting
confidence: 78%
See 1 more Smart Citation
“…At higher tempering temperatures, precipitation of iron rich carbides indicates the decomposition of martensite into ferrite and Fe 3 C, which is slightly enriched with Cr. A similar sequence has been reported for a study on En31 steel [40]. The XRD patterns of the as-quenched, quenched-tempered 523 K, quenched-tempered 723 K and quenched-tempered 923 K D2 steel samples are shown in Fig.…”
Section: 82supporting
confidence: 78%
“…Reduction in the size of the crystallites/coherently diffracting domains and increase in the micro-strain lead to the broadening of the peak profiles. The presence of dislocations in the structure induces micro-strains, which results in the broadening of the diffraction peaks [40,41]. After tempering at 523 K, 723 K and 923 K, the broadening reduced due to reduction in the dislocation density as well as decomposition of martensite into ferrite.…”
Section: 82mentioning
confidence: 99%
“…Though this law gives a very rough and general approximation of wear behavior, it has been successful in describing a first estimate of wear behavior for various materials ( Ref 15). There are numerous studies on steels, which indicate that an increase in hardness results in an increase in the wear resistance (Ref [16][17][18][19]. However, contradictory opinions also exist in the published literature.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors (Ref 20,21) have reported a drop in wear resistance with increase in hardness in steels. These studies (Ref [16][17][18][19][20][21], particularly on the two-body abrasive wear behavior, are mostly confined to steels and Al alloys. A systematic study relating abrasive wear behavior of Ti64 alloy to hardness (and heat treatment) is not available in the domain of published literature.…”
Section: Introductionmentioning
confidence: 99%
“…Application of heat treatment during manufacturing process is one of the most effective ways to improve main service properties of hypoeutectoid low alloy steel products: fire resistance, 1) susceptibility to hydrogen induced cracking and sulfide stress cracking, 2) abrasive wear resistance, 3) strength and toughness. 4) Depending on the cooling intensity of the metastable austenite even before its phase transformation different microstructures with different properties are obtained, 5) especially throughout the cross-section of the products with large diameters.…”
Section: Introductionmentioning
confidence: 99%